Plasma dynamics studies in development of IPD method of surface engineering - Rabiński, M.; Zdunek, K. (Вопросы атомной науки и техники, 2015)
During the Impulse Plasma Deposition (IPD) process of surface engineering plasma is generated in the working gas due to a high-voltage high-current discharge, ignited within an interelectrode region of a coaxial accelerator. The paper presents computational studies of working medium dynamics during the IPD discharge. Plasma has been investigated with a two-dimensional two-fluid magnetohydrodynamic code. Presented analysis of discharges outside the typical exploitation parameter range increases the understanding of phenomena relevant to process of coatings deposition.